Effect of prenotification on the response rate of a postal survey of emergency physicians: a randomised, controlled, assessor-blind trial - Monica Taljaard; Jeffrey J Perry; Lauralyn McIntyre; Kasim Abdulaziz; Michael Hickey; Krishan Yadav; Carly Hickey (BMJ Open)
Objectives Response rates to physician surveys are typically low. The objective of this study was to determine the effect of a prenotification letter on the response rate of a postal survey of emergency physicians.Design This was a substudy of a national, cross-sectional postal survey sent to emergency physicians in Canada. We randomised participants to either receive a postal prenotification letter prior to the survey, or to no prenotification letter.Participants A random sample of 500 emergency physicians in Canada. Participants were selected from the Canadian Medical Directory, a national medical directory which lists more than 99% of practising physicians in Canada.Interventions Using computer-generated randomisation, physicians were randomised in a concealed fashion to receive a prenotification letter approximately 1 week prior to the survey, or to not receive a prenotification letter. All physicians received an unconditional incentive of a $3 coffee card with the survey instrument. In both groups, non-respondents were sent reminder surveys approximately every 14 days and a special contact using Xpresspost during the final contact attempt.Outcome The primary outcome was the survey response rate.Results 201 of 447 eligible physicians returned the survey (45.0%). Of 231 eligible physicians contacted in the prenotification group, 80 (34.6%) returned the survey and among 237 eligible physicians contacted in the no-prenotification group, 121 (51.1%) returned the survey (absolute difference in proportions 16.5%, 95% CI 2.5 to 30.5, p=0.01).Conclusion Inclusion of a prenotification letter resulted in a lower response rate in this postal survey of emergency physicians. Given the added costs, time and effort required to send a prenotification letter, this study suggests that it may be more effective to omit the prenotification letter in physician postal surveys.